Inhaled Remifentanil in Rodents. (June 2016) - Bevans, Tatjana; Deering-Rice, Cassandra; Stockmann, Chris; Light, Alan; Reilly, Christopher; Sakata, Derek J.
Abstract : BACKGROUND: Remifentanil is an injectable opioid that is metabolized rapidly at a constant rate by plasma esterases. This supports its use as an analgesic for short-term, but painful, procedures in a wide range of patients. The aim of this study was to explore the feasibility and safety of administering remifentanil via inhalation. Our hypothesis was that inhaled remifentanil would be absorbed rapidly, pharmacologically active, rapidly cleared, and noninjurious to rodent airways and lungs. METHODS: Rats were exposed to remifentanil aerosol (100–2000 μg/mL) for varying times (1–5 minutes). Analgesia was quantified as a function of dose and time by measuring time to tail flick in response to a painful stimulus. Remifentanil was measured in blood using liquid chromatography-tandem mass spectrometry. Pulmonary mechanics and histology were assessed in mice for the evidence of adverse effects after acute and repeated (subacute) dosing. RESULTS: Exposure of rats to remifentanil aerosols produced dose-dependent analgesia within 2 minutes, which was sustained for the exposure period. Subsequently, the rats experienced rapid and complete recovery with a return to baseline tail flick response to a painful stimulus within 5 minutes. Analgesia mirrored the concentration profile of remifentanil in blood, and the animals were not affected adversely by repeated dosing. Pulmonary mechanics measurements in mice indicated that remifentanil was nonirritating and that the nasal and respiratory tissues of rats were free of significant morphological changes. CONCLUSIONS: Remifentanil delivered by inhalation is rapidly absorbed, pharmacologically active, rapidly cleared, and noninjurious to respiratory tissues in rodents. Abstract : Supplemental Digital Content is available in the text.Published ahead of print March 11, 2016